Polysaccharide oxidation by lytic polysaccharide monooxygenase is enhanced by engineered cellobiose dehydrogenase. (1st October 2019) - Kracher, Daniel; Forsberg, Zarah; Bissaro, Bastien; Gangl, Sonja; Preims, Marita; Sygmund, Christoph; Eijsink, Vincent G. H.; Ludwig, Roland
Abstract : The catalytic function of lytic polysaccharide monooxygenases (LPMOs) to cleave and decrystallize recalcitrant polysaccharides put these enzymes in the spotlight of fundamental and applied research. Here we demonstrate that the demand of LPMO for an electron donor and an oxygen species as cosubstrate can be fulfilled by a single auxiliary enzyme: an engineered fungal cellobiose dehydrogenase (CDH) with increased oxidase activity. The engineered CDH was about 30 times more efficient in driving the LPMO reaction due to its 27 time increased production of H2 O2 acting as a cosubstrate for LPMO. Transient kinetic measurements confirmed that intra‐ and intermolecular electron transfer rates of the engineered CDH were similar to the wild‐type CDH, meaning that the mutations had not compromised CDH's role as an electron donor. These results support the notion of H2 O2 ‐driven LPMO activity and shed new light on the role of CDH in activating LPMOs. Importantly, the results also demonstrate that the use of the engineered CDH results in fast and steady LPMO reactions with CDH‐generated H2 O2 as a cosubstrate, which may provide new opportunities to employ LPMOs in biomass hydrolysis to generate fuels and chemicals. Abstract : Lytic polysaccharide monooxygenases (LPMOs) require an electron donor and an oxygen species as a cosubstrate. We show that a single auxiliary enzyme, an engineered cellobiose dehydrogenase (CDHoxy+ ), provides both. CDHoxy+ produces about 30 times more H2 O2 than the wild‐type CDH and greatly boosts the activity of LPMO. These results demonstrate H2 O2 ‐driven LPMO activity and provide new opportunities for the application of CDH in industrial biomass utilization.